A systematic review protocol for assessing equity in clinical practice guidelines for traumatic brain injury and homelessness - Chan, Vincy; Estrella, Maria Jennifer; Babineau, Jessica; Colantonio, Angela (Frontiers in Medicine, 2022)
Background: When used optimally, clinical practice guidelines (CPGs) can reduce inappropriate variations in practice, improve application of research to practice, and enhance the quality of healthcare. However, a common criticism, despite its potential, is the lack of consideration for equity and disadvantaged populations. Objectives: This protocol is for a systematic review of CPGs for traumatic brain injury (TBI) and homelessness that aims to assess (1) the extent to which evidence regarding TBI and homelessness is integrated in CPGs for homelessness and TBI, respectively and (2) equity considerations in CPGs for TBI and homelessness. Methods and Analysis: The methodology for this review is guided by the PRISMA-P, validated search filters for CPGs, and methodological guides to searching systematic reviews and grey literature. CPGs will be identified from (a) databases for peer-reviewed literature (MEDLINE, Embase, CINAHL, and PsycInfo), (b) targeted websites and Google Search for grey literature, and (c) reference lists of peer-reviewed and grey literature that meets the eligibility criteria. Searching for grey literature, including from guideline-specific resources, is a critical component of this review and is considered an efficient approach to identifying CPGs, given the low precision of searching peer-reviewed databases. Two independent reviewers will screen all articles based on pre-determined eligibility criteria. A narrative synthesis will be conducted to identify the proportion of CPGs that integrate evidence about TBI and homelessness and how TBI and homelessness is or is not integrated in CPGs. Quality appraisal will take the form of an equity assessment of CPGs and will be completed independently by two reviewers. Conclusion: This protocol outlines the methodology for a systematic review of CPGs for TBI and homelessness. The resulting systematic review from this protocol will form an evidence-based foundation to advance CPGs for individuals with lived experience of TBI and homelessness. PROSPERO: CRD42021287696.